The Influence of Product Quality and Price Perception on Purchase Decision through Customer Trust and Customer Satisfaction as Mediating Variables (A Study on Vape Users in Malang City) - Ahmad Gozi; Sudarmiatin; Titis Shinta Dhewi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of product quality and price perception on purchase decisions through customer trust and customer satisfaction among vape users in Malang City. A quantitative approach was applied using purposive sampling, involving 385 respondents, and the data were analyzed using SEM-PLS. The findings show that product quality and price perception have positive and significant effects on customer trust, customer satisfaction, and purchase decisions. Customer satisfaction significantly mediates the effects of product quality and price perception on purchase decisions, while customer trust does not. These results confirm that customer satisfaction is the key driver of vaping consumers’ purchase decisions. Keywords: Product Quality; Price Perception; Purchase Decision; Customer Trust; Customer Satisfaction; Vape